The factors influencing nurse mental Health in hospital raja perempuan zainab ii (hrpz ii) - Mohamad Faizhan Mohd Fauzi; Nur Ain Hakimah Kamal; Nur Ain Solehah Ghazali; Nur Athirah Azman (2023)
Nursing staff work procedures have been associated with emotional anxiety, sadness, psychological discomfort, sleep problems, fatigue and other physical ailments, all of which have a significant impact on the emotional health of these healthcare professionals. The purpose of this study is to determine the impact of organizational, personal problems, stress levels, sleep quality, and financial issues on mental health among nurses at HRPZ II. This is a cross-sectional descriptive study that was conducted among 104 nurses at HRPZ II. Data was obtained using an online questionnaire and processed using SPSS 26.0 software. This study analysed 104 respondents, with 62.5% female and 37.5% male. Respondents were also divided into four age groups, namely 30 years and above (33.7%), 26-29 years (31.7%), 22-25 years (24.9%), and 18-21 years (7.7%). Most of the nurses were married (54.8%), while 45.2% were single. The racial distribution is 76.9% Malay, 14.4% Chinese, 7.7% Indian, and 1.0% Iban. The majority of respondents are Muslims (78.8%), followed by Buddhists (12.5%). The Christian population had the fewest respondents (8.7%). In a bivariate analysis, the results of this study show that there are five factors that affect nurses' mental health, namely organization, personal problems, stress level, sleep quality and finances. Further analysis using Pearson's correlation showed that all hypotheses were rejected at the 0.01 significance level. Independent variables, such as organization, personal problems, stress levels, sleep quality, and finances, have weak positive correlations with mental health. The results of the study show that the majority of respondents are not overly burdened with daily responsibilities and have good mental health. A strong culture that promotes high ethical standards can positively impact employee behaviour.